Perlindungan dan Penegakan Hak Asasi Manusia terhadap Kasus Perbudakan Anak Buah Kapal Indonesia di Kapal Asing - Arum Nur Fadilah Muis (Jurnal Hukum Lex Generalis, 2022)
Ship crew is a job that is in demand by some people because it is based on lucrative wages, but in reality, there are cases of torture and slavery of crew members which are then classified as human rights violations. The government has an obligation in the form of protecting the human rights of Indonesian crew members on foreign ships. Legal protection the government provides consists of two forms: preventive protection and repressive protection. Not only that, in minimizing slavery to the ship crews, the government made efforts to enforce the law in the form of cooperation with other countries to achieve the goal of handling slavery.